An Efficiency and Effectively of Methodology in Software Development Workflow Based on Malaysia - Ibrahim, Zairina; Johar, MD Gapar MD; Rahman, Normy Rafida Abdul (International Journal of Engineering and Technology, 2018)
The process of software development life cycle (SDLC) is an important element of development phases to develop the application. In fact, there are needs to upgrade the sequence of methodology in software development. The SDLC methodology is the highest level of abstraction and is defined as a collection of problem-solving methods governed by a set of principles and common philosophies in solving targeted problems for extended project timeline teamwork as well as a decrease of a high team collaboration and understanding in the software development. Thus, the SDLC is very crucial in order for them to ensure the quality of skills is placed accordingly in the workflow. This research contributes to the development of a new approach in system development workflow with the aim to properly manage system development projects. It started by providing some background data related to the previous mode of operation in the teamwork samples as shared by the stakeholders of the transformation projects and the new proposed Analysis System Development Framework (ASDF) method team members. Then, the key findings related to themes of 1) input for User Requirement Specification (URS) and 2) System Requirement Specification (SRS), 3) proses for module, 4) process for database, 5) process for User Acceptance Testing (UAT) 6) output for Final Acceptance Testing (FAT) and empowerment for the whole level based on ASDF method. This research contributes mainly to the findings, more than previous research has found, that significantly support the perception that a high quality of skills in a teamwork results in better performance of software development.